Design Thinking for Age-Friendly Furniture in Chinese Nursing Homes: Addressing Physiological and Behavioral Characteristics of the Elderly - YUN, ZHANG (Universiti Malaysia Sarawak, 2024)
This research aims to explore the method of addressing the design challenges of age-friendly furniture by optimizing product functionality and implementing innovative design to meet the diverse needs of the elderly in nursing homes in China. Therefore, this research analyse the physiological and behavioral characteristics of the elderly in nursing homes in China, to explore their existing problems and user requirements, to propose the attributes, elements, principles and methods of age-friendly furniture design, and finally to verify the feasibility and effectiveness of the proposed research questions and objectives through design practice. In order to fulfil the objectives of this research and address the research questions, a combination of qualitative and quantitative research methods was utilized to summarise, gather, and analyse the research data, as well as to identify the principal issues and solutions of the research program. This research applies various research techniques, including literature analysis, questionnaires, and interviews, in conjunction with direct observation of specific objects, to conduct a thorough investigation into the current state of furniture usage, design requirements, and physiological and behavioral characteristics of the elderly residing in nursing homes. On this basis, the study analyses the existing problems and causes, design attributes and focal points, as well as user requirements, in relation to the development of age-friendly furniture designs for nursing homes. Furthermore, two brainstorming design workshops are organized to identify keywords, functional hierarchy models, design features, and design concepts for age-friendly furniture design. By analysing the data obtained from the research and conducting a systematic study, this study summarizes seven major user requirements and six major design elements. Subsequently, it proposes seven design principles and a range of design methods tailor to the physiological and behavioral characteristics of the elderly in nursing homes in China. The study proceeds to implement and validate the proposed design principles and methods. Additionally, it highlights the limitations of design practice, future work, and recommendations. Finally, the design practice and validation are executed.